Patient-Reported Quality-of-Life Profile in Patients with Heart Failure with Preserved Ejection Fraction and Type 2 Diabetes: Baseline Findings from a Tirzepatide Study - Laura Danyarova; Ainur Akilzhanova; Rustem Tuleutayev; Yerkezhan Danyarova; Indira Karibayeva; Moldir Zhekeyeva; Aruzhan Zhanuzak (Astana Medical Journal, 2026)
Introduction. Health-related quality of life is impaired in patients with heart failure with preserved ejection fraction and type 2 diabetes mellitus, but clinical factors remain poorly characterized. Baseline assessment is needed to interpret treatment-related changes. Objective. To assess baseline health-related quality of life before tirzepatide therapy, compare the tirzepatide and standard-care groups, and identify clinical, anthropometric, metabolic, and echocardiographic correlates. Methods. Baseline data from a single-center prospective controlled study of 60 patients were analyzed: 30 allocated to tirzepatide and 30 to standard care. Quality of life was assessed before treatment using the 36-Item Short Form Health Survey; complete data were available for 58 participants. Associations were examined using Spearman correlation and multiple linear regression adjusted for age, sex, and treatment group. Results. Patients allocated to tirzepatide were younger and had a higher body mass index. Most domains were comparable. The between-group difference in mental health (p=0.037) did not meet the Bonferroni-adjusted significance threshold. The lowest scores were observed for role limitations due to physical health, role limitations due to emotional problems, and vitality. In adjusted analyses, each 1 kg/m² increase in body mass index was associated with a 1.78-point decrease in physical functioning (p=0.002). Each one-unit increase in the ratio of early transmitral inflow velocity to early diastolic mitral annular velocity was associated with a 2.08-point decrease in general health (p=0.015). No significant associations were found with glycated hemoglobin, N-terminal pro-B-type natriuretic peptide, left ventricular ejection fraction, or global longitudinal strain. Conclusion. Before treatment, the quality-of-life profile was dominated by physical limitations and restrictions in usual activities. Associations with body mass index and estimated left ventricular filling pressure highlight the need to consider metabolic and hemodynamic characteristics when evaluating tirzepatide efficacy. Keywords: quality of life, patient reported outcome measures, diastolic heart failure, diabetes mellitus, tirzepatide.